Psychological disturbance and service provision in parentally bereaved children: prospective case-control study. Issue 7206 (7th August 1999) - Dowdney, Linda; Wilson, Richard; Maughan, B; Allerton, M; Schofield, P; Skuse, D
Abstract: Objectives: To identify whether psychiatric disturbance in parentally bereaved children and surviving parents is related to service provision. Design: Prospective case-control study. Setting: Two adjacent outer London health authorities. Participants: 45 bereaved families with children aged 2 to 16 years. Main outcome measures: Psychological disturbance in parentally bereaved children and surviving parents, and statistical associations between sample characteristics and service provision. Results: Parentally bereaved children and surviving parents showed higher than expected levels of psychiatric difficulties. Boys were more affected than girls, and bereaved mothers had more mental health difficulties than bereaved fathers Levels of psychiatric disturbance in children were higher when parents showed probable psychiatric disorder. Service provision related to the age of the children and the manner of parental death Children under 5 years of age were less likely to be offered services than older children even though their parents desired it Children were significantly more likely to be offered services when the parent had committed suicide or when the death was expected Children least likely to receive service support were those who were not in touch with services before parental death. Conclusions: Service provision was not significantly related to parental wishes or to level of psychiatric disturbance in parents or children. There is a role for general practitioners and primary care workers in identifying psychologically distressed surviving parents whose children may be psychiatrically disturbed, and referring them to appropriate services.